Social protection experiences of and attitudes towards new urban poor after Covid-19 in Bangladesh - Roelen, Keetie; Diwakar, Vidya; Huq, Lopita; Sultan, Maheen; Ahmed, Md. Shakil; Chowdhury, Kabita; Al Mamun, Saklain; Rabbi, Abu Sayem; Rahman, Nuzaba Tahreen; Rownak, Raisa; Sumanthiran, Shilohni (Institute of Development Studies, 2024)
The Covid-19 pandemic led to a large increase in poverty in Bangladesh, especially in urban areas. Rising food prices and high inflation rates further compounded already high levels of socioeconomic uncertainty. Social protection is vital to help mitigate the effects of crisis and make households more resilient to uncertainty. This paper provides insights into urban residents’ experiences of poverty and the support they received since the Covid-19 pandemic, and derives implications for social protection programming in urban Bangladesh. Using secondary longitudinal data collected since the start of the pandemic with new quantitative surveys and qualitative data collected in Kallyanpur, Dhaka and Shantinagar, Chittagong in March 2023, the study points to high levels of precarity; poverty’s toll on mental health; widespread stigmatisation and discrimination of residents of low-income neighbourhoods, and inadequate social protection support. It argues for the need to expand social protection in urban areas; counter area-based discrimination; ensure dignified delivery of assistance, and provide an integrated policy response.